Ear magnetic discs to prevent cauliflower ear: a case gone wrong. Issue 11 (10th November 2022) - Ang, Wan Wei; Foley, Gary; Laycock, Juliet; McKay-Davies, Iain
Abstract : We present a case of pinna pressure necrosis secondary to the use of ear magnetic discs, used in the management of auricular haematoma. A man in his 20s sustained a left auricular haematoma while wrestling. His coach aspirated the haematoma and advised the use of commercially available compression magnets on either side of the pinna to prevent haematoma reaccumulation. 5 days later, he presented to accident and emergency with left ear pain and swelling. Perichondritis was evident on examination and the compression magnets were removed to reveal significant pressure necrosis of the pinna. The skin underlying the placement of magnets (both anteriorly and posteriorly) was black and necrosed, with erosion of the underlying cartilage. In addition to this, the haematoma had reaccumulated in the surrounding pinna. The haematoma was drained via an incision, and pressure dressing applied with dental rolls. The patient was given a course of oral antibiotics to manage the perichondritis. He was reviewed regularly in the ear, nose and throat emergency clinic to monitor wound healing. 3 months later, he was reviewed in the otology clinic; there was persistent helical rim deformity, and delayed cartilage augmentation was advised. This case highlights the importance of prompt and effective management of auricular haematoma, to prevent long-term deformity. Commercially available pinna magnets for auricular haematoma should be used with caution, and patients should be counselled as such.